The security function of the community protection unit in the Teling Atas Urban Village, Manado City - Kandung, Richard; Mokat, Jetty E. H; Bulo, Laurens (Technium Social Sciences Journal, 2024)
This research aims to find out, analyze and describe 1) The Security Function of the Community Protection Unit (Satlinmas) in Teling Atas urban village, Manado City has not run optimally, and 2) Determinant factors of the Security Function of the Community Protection Unit in Teling Atas urban village, Manado City. This research used a qualitative research design with a contextual research that makes humans as instruments and is adapted to a natural situation in relation to data collection which is generally qualitative in nature. The results showed that 1) in terms of Member Capacity, so far Satlinmas members in Teling Atas urban village, Manado City have never participated in education and training; 2) in terms of Facilities and Infrastructure, in carrying out security tasks, Satlinmas has not been supported by adequate facilities and infrastructure; 3) in terms of Coordination with the provincial government, district / city, sub-district to the village / urban village level is quite good but not optimal. While coordination with local residents is quite well established; 4) in terms of Budget, there is no budget organized in the Manado City Regional Budget (APBD) through Teling Atas Urban Village for operational costs of carrying out security patrol tasks, procurement of uniforms, supporting equipment for Satlinmas members as well as monthly allowances/honors; 5) in terms of Community Participation, Community participation is very limited.